Crosstalk Between Chaperone-Mediated Protein Disaggregation and Proteolytic Pathways in Aging and Disease - Feleciano, Diogo R.; Juenemann, Katrin; Iburg, Manuel; Brás, Inês C.; Holmberg, Carina I.; Kirstein, Janine (Frontiers in Aging Neuroscience, 2019)
A functional protein quality control machinery is crucial to maintain cellular and organismal physiology. Perturbation in the protein homeostasis network can lead to the formation of misfolded and aggregated proteins that are a hallmark of protein conformational disorders and aging. Protein aggregation is counteracted by the action of chaperones that can resolubilize aggregated proteins. An alternative protein aggregation clearance strategy is the elimination by proteolysis employing the ubiquitin proteasome system (UPS) or autophagy. Little is known how these three protein aggregate clearance strategies are regulated and coordinated in an organism with the progression of aging or upon expression of disease-associated proteins. To unravel the crosstalk between the protein aggregate clearance options, we investigated how autophagy and the UPS respond to perturbations in protein disaggregation capacity. We found that autophagy is induced as a potential compensatory mechanism, whereas the UPS exhibits reduced capacity upon depletion of disaggregating chaperones in C. elegans and HEK293 cells. The expression of amyloid proteins Aβ3-42 and Q40 result in an impairment of autophagy as well as the UPS within the same and even across tissues. Our data indicate a tight coordination between the different nodes of the proteostasis network with the progression of aging and upon imbalances of the capacity of each clearance mechanism.